Potential Application of Consortium Microbe from Sea Cucumber Intestinal Symbiont as Preservatives for Vaname Shrimp - Marwa Irfan Hanif; Delianis Pringgenies; Gunawan Widi Santosa (Research Centre of Inorganic Materials and Complexs, 2019)
Vaname shrimp is one of the most profitable export commodities in Indonesia. However, the shrimp meat undergoes rapid quality degradation when shipped without any preservatives. This is an issue since the preservatives commonly found on the market are formalin-based. This study aims to discover a natural preservative solution by utilizing microbes. The objective of the study is to discover natural preservatives made of symbiont microbe in sea cucumber's intestinal organ by antimicrobial activity screening. Sea cucumber samples were collected from Bandengan waters of Jepara. There are 3 symbiotic microbe form intestinal cucumber that can inhibit the growth from Bacillus cereus and Pseudomonas aeruginosa. These three microbes are Listeria sp., Staphylococcus sp., and Rothia sp. Consequently, tested microbial samples were prepared into a consortium microbe and were tested further as a preservative agent for shrimp with a positive control parameter (cooling). The observations conducted in this study include organoleptic properties, acidity, total colony, proximate test (protein, water, ash, fat, and carbohydrate contents), and Total Volatile Base-Nitrogen (TVBN). The results found 3 active isolates are synergic one to each other as a bacterial consortium. Acidity test of sample extract treatment measured a pH of 7.44, compared to the non-treatment result of 7.14. Organoleptic test results of the shrimp indicated that the shrimp was acceptable for consumption. Proximate test of the treatment did not show a significant difference compared to the positive control treatment. Total colony and TVBN test on treated samples resulted in 48 x 105 CFU/ml and 39.62 mgN% respectively, whereas a similar test on non-treatment sample showed 119 x 105 CFU/ml and 45.31 mgN% respectively. It was concluded that the extract of sea cucumber symbiont microbe consortium showed potency in preventing meat quality degradation in shrimp, although treatment by freezing still produces a better result.